The Effect of Physical Treatment and Storage Time on The Quality of Sugar Cane Juice - Septyan Aindr Irawan; Sentosa Ginting; Terip Karo-Karo (Universitas Sumatera Utara, 2015)
The aim of this study was to maintain the quality of sugar cane juice by physical treatments on the sugar cane juice by cooling at 5oC the prescribed periode, heating at 85oC until 5 minutes, as well as combine of heating at 85oC until 5 minutes and cooling at 5oC the prescribed periode, and control for the 1, 3, 5, and 7 days. Study was conducted in the Laboratory of Food Technology, Program study Food and Science Technology, Faculty of Agriculture USU, Medan, using factorial completely randomized design. The parameters analyzed were total sugars, ash, total microbes, pH, total acid, total soluble solid, and organoleptic values of color, aroma, and taste. The results showed that the physical treatment and storage time gave highly significantly different effect on all parameters except for ash. The interaction of the two factors had highly significantly affected all parameters except total soluble solid and ash. Sugar Cane juice that was had of heating at 85oC until 5 minutes and cooling 5oC the prescribed periode the best quality of phisico chemical within the prescribed period. Keywords : Physical treatment, Storage time, Sugar Cane Juice